dataset_crypto_energy_final_level.xlsx - Muhammad Shahbaz (21597971) (2025)
This study employs monthly data from January 2000 to October 2022. The estimation sample is dictated by the availability of energy-related uncertainty variables. The core variable of the model is a cryptocurrency environmental attention index (ICEA). This index is calculated by Wang et al. (2022).The index of global geopolitical risks (GPR), developed by Caldara and Iacoviello (2022), is another important variable in the model. Furthermore, the financial stress index (FSI), developed by Office of Financial Research, is utilized. Finally, the energy-related uncertainty index (EU), developed by Dang et al. (2023)